2003
DOI: 10.1002/jrs.1053
|View full text |Cite
|
Sign up to set email alerts
|

Skin/bulk nanostructure and corrosion of SiC‐based fibres: a surface Rayleigh and Raman study

Abstract: SiC-based fibres are complex systems of nanophases. Raman imaging of polished Tyranno SA3 fibre (UBE Industry) sections indicated that carbon species have different concentrations, natures and short-range order on the fibre core and surface, which results from the production process. The monitoring of the fibre's skin/bulk nanostructure, composition and geometry was performed on sections by Raman and Rayleigh microspectrometry. Owing to the weak light penetration in these materials, Rayleigh diffusion can map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…9 In the case of Raman/Rayleigh images containing several hundred spectra, LabSpec 2.0 software was used. Raman images were recorded using the Infinity spectrometer with …”
Section: A Labram Infinity Microspectrometer (Jobin-yvon-mentioning
confidence: 99%
See 1 more Smart Citation
“…9 In the case of Raman/Rayleigh images containing several hundred spectra, LabSpec 2.0 software was used. Raman images were recorded using the Infinity spectrometer with …”
Section: A Labram Infinity Microspectrometer (Jobin-yvon-mentioning
confidence: 99%
“…8 Raman and Rayleigh imaging have helped in the identification of the skin/core (nano)structure. 9 Recently, the use of Raman spectroscopy has shown that a similar phenomenon occurs in polyaniline fibres spun in the gel state. Such a particular skin/core structure has been related to solvent evaporation and surface reaction.…”
Section: Introductionmentioning
confidence: 99%
“…2), are corresponding to the diamond-like carbon and the graphitic carbon, respectively [10]. The diamond-like carbon occurs when C inhabits the Si site in the SiC lattice, which means the Si-vacancy (V Si ) more easily existing in the same position.…”
Section: Resultsmentioning
confidence: 99%
“…The single, smooth and continuous curve of these compounds can be ascribed to the S 2 type, according to the Giles classification scheme. This type of curve is typical for micro-porous sorbents and was observed in the monolayer sorption on the microporous adsorbent [45].…”
Section: Effect Of Contact Time and Initial Concentrationmentioning
confidence: 97%
“…The results of Boehm titration of silicon carbide particles in the present study (Table 1), indicate that the specific surface charge of the SiC powder was positive. On the other hand, Haval and Colomban [45] showed the existence of unsaturated hydrocarbons on the surface of silicon carbide particles. Also, the reaction of unsaturated hydrocarbons on silicon carbide nanoparticles with radical species generated from azo radical imitators has been reported [46].…”
Section: Acmentioning
confidence: 98%